Development of lightweight high‐performance polymeric composites with functionalized nanotubes. Issue 21 (16th February 2016) - Vijayan, Vigil Jasmin; Arun, A.; Bhowmik, Shantanu; Abraham, Mathew; Ajeesh, G.; Pitchan, Mohan Kumar
ABSTRACT: In this article, we highlight the various properties of an ultralightweight poly(ether ketone) (PEK) composite. In this study, special emphases were laid on the preparation of low‐density, high‐performance polymeric foams with foaming agents and activators. PEK, foamed PEK, and carbon nanotube (CNT)–reinforced foamed PEK composites were considered for this study. The density of the polymer decreased with the reinforcement of the foaming agent. We also noted that with the reinforcement of the modified CNT in the foamed PEK, there were marginal increases in the density and hardness of the composites. We also noted that the mechanical properties of the CNT‐reinforced foamed PEK was on par with those of basic PEK. Thermogravimetric analysis gave us a clear indication that the thermal stability of the composites was not affected by the reinforcing foaming agent and nanoparticles. Scanning electron microscopy and transmission electron microscopy clearly indicated the formation of foams and also the dispersion of nanoparticles in the composite structure. We also observed that because of the reinforcement of multiwalled CNTs in the composite, there was an improvement in the hardness of the composite. An increase in the specific strength was observed in the foamed PEK composites. The CNT‐reinforced foamed PEK showed a marginal decrease in the specific strength without a compromise in the impact strength. The impact strength of the CNT‐reinforced foamed PEK composite was found to be similar to that of the basic PEK. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43471. Abstract :